Evaluating the acetylcholinesterase inhibitory activity of Ferulago angulata and Ferulago subvelutina - H. Hajimehdipoor; M. Shekarchi; A. Aghighi; M. Hamzeloo-Moghadam (Iranian Society of Pharmacognosy, 2014)
Alzheimer is an age-dependent disease mostly with genetic origin. In this disorder, acetylcholine is decreased which results in deterioration of short-term memory. Many researches have been focused on finding new sources of medications with more potency and less side effects and investigating acetylcholinesterase inhibitors (AChEIs) has been the center of many researches. In the present study, the acetylcholinesterase inhibitory property of the total extracts and fractions of Ferulago angulata and Ferulago subvelutina have been evaluated according to Ellman method. The total extract and the 50% methanol fraction of Ferulago angulata demonstrated weak AChEI activity (15.8% and 9% in concentration of 300 μg/mL, respectively). The ability of the total extract and the n-hexane, dichloromethane, ethyl acetate and 50% methanol fractions of Ferulago subvelutina were found to be 19.7%, 15.4%, 32.2%, 14.5% and 11.7%, respectively. It was concluded that among the evaluated extracts and fractions, the dichloromethane fraction of Ferulago subvelutina demonstrated reasonable AChEI activity and it is suggested for further purification of its components.